1989
DOI: 10.1002/jobm.3620290806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic soil amendments on the incidence of brown spot disease in maize caused by Physoderma maydis

Abstract: Six organic materials were added to the soil in a field recently showing a high incidence of brown spot disease in maize caused by Physoderma maydis. All the amendments lowered significantly the occurrence of the disease in comparison to the unamended control. However, the ability to suppress the disease differed substantially among the amendments. Rice bran and rice straw were most effective in this respect. The suppression of the disease appeared to be related to an increased microbial activity in the soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…This conforms to the findings of Obagwu et al [25] who reported Mancozeb as the most effective fungicide in inhibiting the growth of Colletotrichum capsici responsible for brown blotch of Bambara nut. Similar result was presented by Osunlaja and Alamutu [26] who also reported the effectiveness of Mancozeb in inhibiting the growth of Physoderma maydis (brown spot).…”
Section: Bio-efficacy Of Some Plant Extractssupporting
confidence: 87%
“…This conforms to the findings of Obagwu et al [25] who reported Mancozeb as the most effective fungicide in inhibiting the growth of Colletotrichum capsici responsible for brown blotch of Bambara nut. Similar result was presented by Osunlaja and Alamutu [26] who also reported the effectiveness of Mancozeb in inhibiting the growth of Physoderma maydis (brown spot).…”
Section: Bio-efficacy Of Some Plant Extractssupporting
confidence: 87%
“…The effectiveness of soil amendment in controlling soil-borne plant disease was well documented (Osunlaja, 1989;Oritsajafor and Adeniji, 1990;Hadar and Mendaelbaum, 1992;Vos and Duriant, 1995). In this study with the exception of neem leaf amended soil significant differences in the amended and un-amended treatments were observed.…”
Section: Discussionmentioning
confidence: 43%
“…Controls consisted of a set of non inoculated pots for each age treatment and a set of inoculated unamended soil. Fungal populations in the amended soils and the control were determined by dilution plates method of Osunlaja (1989), using a soil dilution of 10~3 on potato dextrose agar to which the antibacteria supplement streptomycine had been added. The fungal colonies were counted on counting chambers, multiplying the numbers of colonies by dilution factors to obtain number of colonies per gram of soil.…”
Section: Soil Amendmentmentioning
confidence: 99%